Distributed Hybrid Networks: Estimating Bandwidth Controlled Topological Architecture Using an Innovative Approach (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
At present, all things have become very compact, in case of communication they can be defined by different attributes like - digital documents, internet Medias, tele-medicines etc. People have become internet dependent these days. Now a days communication over the internet like – Skype, messengers, g-talk are very familiar tools for chatting. Facebook is also an all-in-one communication media these days. But these software applications that most of the people use need more bandwidth. As a number of enormous internets using people are increasing day by day for that a proper way is needed to control and distribute bandwidth within a conjugated network nodes or network clouds. These days’ people prefer video chatting for more secured and dedicated communication. To send videos as data packets consider the topologies such as- mesh, bus, ring, star, hybrid within the communication networks which uses unlimited bandwidth results a huge wastage but creates a problem for the higher growth of internet users. Thinking of this a controlled algorithm for bandwidth optimization as well as bandwidth management is developed. This algorithm is developed considering a video communication system that has the ability of running PABX, Fax, video via-web conference, video presentation for a defined time through the creation of admin defined extensions. The algorithm has developed considering a local LAN (no internet) and can process user defined data by checking the processing capacity of a processor that ensures 0% drop probability of packets which make it special. The overall mechanism shows better possibilities as an estimation scheme throughout the network nodes to ensure the administrators to design a proper and better network for any distributed network architectures. After evaluating the results, it is assured that this topology works better than any other existing topologies for a distributed system that follows M/M/1 queuing theory.